Reduction of Azomethine Bond of Organic Compound: Part-2. Formation of Aldimine and Ketimine and their Catalytic Hydrogenation: Reduction of Azomethine Bond of Organic Compound: Part-2. Formation of Aldimine and Ketimine and their Catalytic Hydrogenation - Patil, C. J. (International Journal of Pharmaceutical & Biological Archive, 2019)
Azomethine compounds were prepared from Benzaldehyde and o-hydroxy-acetophenone with aniline and o-Nitroaniline. The azomethine bond in the compound is reduced using NaBH4 in 0.1 N sodium hydroxide solution. The reaction is monitored by thin-layer chromatography (TLC) and ultraviolet–visible (UV-Vis) spectral method. Etheral layer is concentrated to get the reduction product. The final products were analyzed by a physical constant, TLC, and spectral techniques such as UV-Vis and Fourier-transform infrared.